2014
DOI: 10.1097/mpg.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐Soluble Vitamins in Cystic Fibrosis and Pancreatic Insufficiency

Abstract: Objectives To assess the impact of LYM-X-SORB™ (LXS), an organized lipid matrix that has previously been shown to be absorbable without pancreatic enzyme therapy on fat soluble vitamin status in children with CF and PI. Methods Children with CF and PI were randomized to daily LXS or an iso-caloric placebo comparison supplement for 12 months. Serum vitamins A (retinol), D (25-hydroxyvitamin D[25D]), E (α-tocopherol, α-tocopherol:cholesterol ratio) and K (%undercarboxylated osteocalcin [%ucOC] and plasma prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
0
20
0
5
Order By: Relevance
“…The complete inclusion/exclusion criteria, study design and method details, Encala™ composition and the results for Encala™ impact on choline and fatty acid status on the full study cohort have been previously reported [10][11][12]. Liver disease and any other significant diagnosis that might impact dietary intake, growth or body composition were exclusion criteria for subjects to participate in this study.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…The complete inclusion/exclusion criteria, study design and method details, Encala™ composition and the results for Encala™ impact on choline and fatty acid status on the full study cohort have been previously reported [10][11][12]. Liver disease and any other significant diagnosis that might impact dietary intake, growth or body composition were exclusion criteria for subjects to participate in this study.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…This finding is of special interest as there are highly concentrated preparations of fat-soluble vitamins available on the market nowadays. It must be borne in mind that these modern products, providing the fat-soluble vitamins in a water-soluble form, guarantee not only efficient supplementation but also present the risk of oversupply and toxicosis [43,44,45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…W przypadku witaminy K dokonuje się pomiaru stężenia białka indukowanego niedoborem witaminy K (Protein Induced by Vitamine K Absence, PIVKA II), które powinno wynosić < 2 ng/ml. Stężenie w osoczu krwi witaminy E powinno kształtować się na poziomie > 5,4 mg/g [41][42][43][44][45]. Badania stężenia witamin rozpuszczalnych w tłuszczach we krwi u osób z CF muszą być wykonywane nie rzadziej niż raz do roku, a po modyfikacji dawki po 3-6 miesiącach [3].…”
Section: Suplementacja Dietyunclassified